Histomorphological Study On Thymus Of Goat During Prenatal Development - Gautam, A.K.; Mishra, U.K.; Mandal , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
In thymus of prenatal goat the capsule and interlobular septa were thin and thickness is increased up to 142 days of gestation. The lobules had dark stained large cortex and contained blood vessels, isolated RBCs, lymphocytes and reticular cells. Medulla revealed moderate eosinophilia and cortex was strongly basophilic by 50th day of gestation. By 99 days more number of reticular epithelial cells and its concentration was increased in 112 days of gestation. At this stage some location of medulla has 2-3 epithelial cells which depicted the initial appearance of thymic corpuscles and by 120 days three types of vacuoles were seen which initiate the thymic corpuscles formation by coliation. By 130 and 142 days thymic corpuscles were enlarged and reticular epithelial cells were numerous in medulla. Similar structural feature in day old neonates were also noted. The concentration of Collagen fibres is increased with age in capsule and septa. Reticular fibres formed a thin layer in capsule and thick layer in septa but it was not observed either in cortex or in medulla till 112 days of gestation. A fine reticular net appeared to circumscribe the cortical and medullar cell types by 142 days of gestation and onwards. Elastic fibres could not be demonstrated in the thymus of goat foeti of any age.